The clinical value and cost-effectiveness of treatments for patients with coronary artery disease - Huang Weiting; Alwin Zhang Yaoxian; Yeo Khung Keong; Shao-Wei Lam; Lau Yee How; Anders Olof Sahlén; Ahmadreza Pourghaderi; Matthew Che; Chua Siang Jin Terrance; Nicholas Graves (Health Economics Review, 2022)
Background The clinical value and cost-effectiveness of invasive treatments for patients with coronary artery disease is unclear. Invasive treatments such as coronary artery bypass grafting and percutaneous coronary intervention are frequently used as a starting treatment, yet they are much more costly than optimal medical therapy. While patients may transition into other treatments over time, the choices of starting treatments are likely important determinants of costs and health outcomes. The aim is to predict by how much costs and health outcomes will change from a decision to use different starting treatments for patients with coronary artery disease in an Asian setting. Methods A cost-effectiveness study using a Markov model informed by data from Singapore General Hospital was done. All patients with initial presentations of stable coronary disease and no acute coronary syndromes who received medical treatments and interventional therapies were included. We compare existing practice, where the starting treatment can be medical therapy or stent percutaneous coronary interventions or coronary artery bypass grafting, with alternate starting treatment strategies. Results When compared to 'existing practice' a policy of starting 14% of patients with coronary artery bypass grafting and 86% with optimal medical therapy showed savings of 1,743 per patient and 0.23 additional quality adjusted life years. A change to policy nationwide would save 10 million and generate 1,380 quality adjusted life years. Conclusions Increasing coronary artery bypass grafting and use of medical therapy in the setting of coronary artery disease is likely to saves costs and improve health outcomes. A definitive study to address the question we investigate would be very difficult to undertake and so using existing data to model the expected outcomes is a useful tool. There are likely to be large and complex barriers to the implementation of any policy change based on the findings of this study.
Keywords: 330; Coronary artery bypass grafting; Percutaneous coronary intervention; Optimal medical therapy; Costeffectiveness